The MAK‐Collection for Occupational Health and Safety 2012
DOI: 10.1002/3527600418.mb12299kskd0026
|View full text |Cite
|
Sign up to set email alerts
|

2‐Phenoxyethanol [MAK Value Documentation in German language, 1998]

Abstract: Veröffentlicht in der Reihe Gesundheitsschädliche Arbeitsstoffe , 26. Lieferung, Ausgabe 1998 Der Artikel enthält folgende Kapitel: Allgemeiner Wirkungscharakter Wirkungsmechanismus Toxikokinetik und Metabolismus Aufnahme Metabolismus Verteilung und Ausscheidung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…6 Animal studies showed that the main metabolite of PhE in urine is phenoxyacetic acid (PhAA) and its conjugates. 9 Unmetabolized PhE or conjugated PhE, however, was also identied in urine, albeit to a much lesser extent of <5% of the administered dose. 6 Furthermore, some minor metabolites such as ring-hydroxylated species, including 4-OH-PhAA, were found in urine samples aer exposure to PhE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Animal studies showed that the main metabolite of PhE in urine is phenoxyacetic acid (PhAA) and its conjugates. 9 Unmetabolized PhE or conjugated PhE, however, was also identied in urine, albeit to a much lesser extent of <5% of the administered dose. 6 Furthermore, some minor metabolites such as ring-hydroxylated species, including 4-OH-PhAA, were found in urine samples aer exposure to PhE.…”
Section: Introductionmentioning
confidence: 99%
“…Two human volunteer studies reported only the identication of phenoxyacetic acid (PhAA) in human urine following oral or dermal exposure to PhE. 9 Data on other PhE metabolites in humans or specic toxicokinetic data following oral and dermal human exposure is not yet available. 6 The postulated metabolic phase-I pathway of PhE is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%